2015
DOI: 10.1186/s12933-015-0287-z
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of YKL-40 and adiponectin and subclinical atherosclerosis in asymptomatic patients with type 1 diabetes mellitus from a European Mediterranean population

Abstract: BackgroundThe glycoprotein YKL-40 is a new marker of early inflammation and endothelial dysfunction. Adiponectin is a collagen-like protein with anti-atherogenic and anti-inflammatory effects. Increased concentrations of both markers have been reported in patients with type 1 diabetes (T1D).AimTo assess the possible role of YKL-40 and adiponectin as a marker of subclinical cardiovascular disease in asymptomatic patients with type 1 diabetes with no history of ischemic or macrovascular heart disease and its rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 29 publications
2
10
0
Order By: Relevance
“…Some studies showed a correlation between CHI3L1 and glycaemic parameters such as HbA 1c , albuminuria [82] and fasting glucose [76]. In concordance with the previous studies performed in T1DM [82,85], significantly higher concentrations of CHI3L1 and adiponectin were found in T1DM patients from a Mediterranean area with a longer disease evolution but a low atherosclerotic background [86]. A study investigating CHI3L1 in relation to mortality in a population with T2DM demonstrated that high levels CHI3L1 predict all-cause mortality and cardiovascular mortality in these patients [76].…”
Section: Chi3l1 and Diabetessupporting
confidence: 76%
See 1 more Smart Citation
“…Some studies showed a correlation between CHI3L1 and glycaemic parameters such as HbA 1c , albuminuria [82] and fasting glucose [76]. In concordance with the previous studies performed in T1DM [82,85], significantly higher concentrations of CHI3L1 and adiponectin were found in T1DM patients from a Mediterranean area with a longer disease evolution but a low atherosclerotic background [86]. A study investigating CHI3L1 in relation to mortality in a population with T2DM demonstrated that high levels CHI3L1 predict all-cause mortality and cardiovascular mortality in these patients [76].…”
Section: Chi3l1 and Diabetessupporting
confidence: 76%
“…Subclinical inflammation is also involved in the pathogenesis of all stages of atherosclerosis [86], where the induction of acute-phase reactants, proinflammatory cytokines and cell adhesion molecules are associated with the development of myocardial infarction, stroke and peripheral vascular disease, and consequently with cardiovascular mortality [95]. Dysfunction of the endothelium is well known in DM and is theearliest event in atherogenesis, playing a pivotal role in all phases of the atherosclerotic process (from the initiation of the fatty streak to plaque rupture), and is largely responsible for the development of ischaemic heart disease and thrombotic strokes [96].…”
Section: Chi3l1 Atherosclerosis and Cardiovascular Complicationsmentioning
confidence: 99%
“…Secondly, patients with systemic autoimmune diseases, such as rheumatoid arthritis or systemic lupus erythematosus, have an increased risk of atherosclerosis, with both cellular and humoral components of the immune system involved in its pathogenesis and some shared genetic risk [ 50 ], although the precise mechanisms underlying the high cardiovascular risk in these patients is unclear [ 51 ]. It is well known that chronic inflammation plays an important role in atherogenesis [ 52 , 53 ], and inflammatory markers associated with macrovascular disease are elevated both in patients with type 1 diabetes and type 2 diabetes [ 54 , 55 ]. Moreover, poor glycemic control and hypoglycaemic episodes are related to pro-inflammatory status [ 56 , 57 ], and may be additional contributing factors in atherosclerosis in patients with autoimmune diabetes [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Longitudinal data is being collected in this cohort as part of the AdDIT Observational Study and will help to clarify the relationships between these physiological measures and clinical outcomes. Finally, this study in adolescents was not designed to elucidate physiological mechanisms responsible for between group differences in cardiovascular function, such as early changes in nitric oxide bioavailability, autonomic tone, vitamin D levels or inflammatory biomarkers [ 60 63 ]. These important modulators of cardiovascular function should be further examined in adolescents in future work.…”
Section: Discussionmentioning
confidence: 99%